(untitled) (World Bulletin of Social Sciences, 2026)
To orient students towards independent research work and to develop creative activity. Organization of students’ research activities, activity over research work, analysis, conclusion, forecasting of the development of the process, conducting a creative study of the object by means of research methods, drawing up a general conclusion, and presentation. Stages of identifying gifted students, skills that hunters acquire in research activities.